Optimization of growth conditions of Hirudinea sp - Zulhisyam Abdul Kari @ Abdullah; Ahmad Anwar Mohamed Ismail; Ibrahim Che Omar (2011)
Leeches (Phylum: Annelida, Class: Hirudinea) are widely distributed all over the world in various habitats, such as freshwater, seas, desert, and oases (Gouda, 2006). In this study, the effect of light intensity, temperature and diet on the reproductive efficiency of Hirudinea sp. was examined with eight different conditions. After 3 months of culture, the number of cocoons produced was very significantly different among the different conditions (p=0.00). The average number of hatchlings per cocoon was significantly different (p # 0.05) where condition 1 gave the highest number (6.23±0.25), but hatching rate was not (p=0.354). The condition 5 produced the highest mortality of parent leeches (52±13.86%). The sizes of the cocoons were not significantly different among the treatments, with the condition 1 having the largest cocoon of 22.19±0.92mm and 13.26±0.07mm according to their length and diameter, respectively. The wet weight of cocoons was significantly different (p # 0.05) with the condition 1 producing the heaviest cocoons of 1.26±0.11g compared to condition 5 producing the lightest cocoons of 0.22±0.38g. The effect of diet (FT1: fresh eel blood and FT2: booster) on the growth and survivorship of the juvenile leeches was also studied. After 2 months of culture, the final body weight was significantly different among the treatments, with juveniles in the FT1 (fresh eel blood) had the highest final body weight (0.8893±0.012g). Percentage weight gain (WG) and specific growth rate (SGR) of the juveniles in the treatment FT2 (booster) were lowest with mean and standard deviation of 769.41±11.54% and 3.6±0.02%, respectively. Juveniles in the FT2 (fresh eel blood) treatment had the highest survival rate (93.33±5.77%).